ISCHEMIA-MODIFIED ALBUMIN (IMA) AS A BIOMARKER OF OXIDATIVE STRESS IN PREGNANCY - Arief Budiono; Dhyfa, Najwa aulia; Julia Windi Gunadi; Ardo Sanjaya (Fakultas Kedokteran Universitas Sriwijaya, 2025)
This study aims to determine IMA levels as a marker of oxidative stress that occurs in ectopic pregnancy and preeclampsia. The method of this study is screening using secondary data obtained from literature searches found in national and international journals, with the keywords 'Oxidative Stress' or 'IMA' and 'Pregnancy'. Articles are included in the inclusion criteria if they are published in national or international journals with topics in accordance with the research objectives in the period 2014 - 2024, full-text access, both in English and Indonesian. It was found that serum IMA levels were increased in preeclampsia and, In comparison to normal pregnancy, ectopic pregnancy. This literature study concludes that IMA can be a biomarker for pregnancy-related diseases, especially preeclampsia and ectopic pregnancy. Higher sensitivity and specificity results in preeclampsia compared to ectopic pregnancy, the IMA test is better used to identify preeclampsia compared to ectopic pregnancy.